Kualitas Pelayanan Administrasi Kependudukan Kepada Masyarakat Pembuat Akte Kelahiran di UPT Dispendukcapil Kecamatan Purwosari - M Daimul Abror; Lu'lu'ul Hidayah (Universitas Dr. Soetomo Surabaya, 2021)
In the implementation of public services, the state civil apparatus is responsible for providing excellent service in order to realize the welfare of the community, especially in the field of population administration, one of which is a birth certificate. This research is motivated by the problem of not yet optimal quality of service for making child birth certificates at the UPT Dispendukcapil Purwosari District seen from the lack of understanding of service procedures, inadequate facilities and infrastructure and community assumptions about the timeliness of the promised not appropriate.The purpose of this study is to describe, analyze, and interpret the quality of service in making child birth certificates and the obstacles that occur in the issuance of birth certificates for children out of wedlock at UPT Dispendukcapil Purwosari District. The research method used is a qualitative method with data sources obtained from interviews, observations and documentation.The results showed that the quality of service for making birth certificates at the UPT Dispendukcapil Purwosari District was quite good but there were several indicators that were still not fulfilled and there were obstacles found such as inadequate infrastructure which had implications for the slow service process and understanding of the community who did not understand. the procedure for making a child's birth certificate so that people think it is slow in terms of timeliness of issuance